BATIK IMMERSION: Development of a Virtual Reality–Based Batik Literacy Media for Strengthening Cultural Literacy and Moral Values - Alya Nabilah Hasna Lubis; Faiza Fitri; Junita Putri; Raida Thalyta Salsabila Putri Andifa (Jurnal Penelitian Medan Agama, 2025)
This research is motivated by the need for innovative learning media to introduce batik as an Indonesian cultural heritage that has been recognized by UNESCO since 2009 and has great potential to be promoted to the global community. This research aims to develop BATIK IMMERSION, a Virtual Reality (VR)-based batik literacy media that provides an immersive, interactive, and contextual learning experience so that users not only understand batik as an art product, but also as a cultural identity that has moral values and strengthens human dignity through the preservation of national heritage. The development was carried out using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) which includes user needs analysis, learning flow design, virtual environment creation, implementation of batik process exploration features, and evaluation of media effectiveness. The evaluation results show that BATIK IMMERSION is able to increase user understanding of the meaning, process, and cultural values of batik, as well as encourage appreciation across social and cultural backgrounds. This media also increases learning engagement through visual interactions and exploratory experiences that are more engaging than conventional learning. Thus, BATIK IMMERSION contributes as a digital technology-based cultural literacy innovation that supports the sustainable preservation of batik and expands the promotion of Indonesian culture at the global level.